Sosialisasi Nilai Ekowisata Mangrove pada Guru dan Siswa SMP di Lembar Kabupaten Lombok Barat - Santoso, Didik; syukur, Abdul; Merta, , I Wayan (Universitas Mataram, 2023)
The function of the mangrove ecosystem is to provide environmental services as a place to share ecological values. One of them is as a direct learning resource for students in understanding science concepts. Utilization of the environmental services of the mangrove ecosystem in the educational aspect is lacking in school areas in the West Lombok Regency. This service activity aims to increase the utilization of the function of the mangrove ecosystem as a natural laboratory and make it an object of research for various scientific and multi-disciplinary developments so that there is a change in the mindset of visitors and students at Mataram University that South South Sheet is not only a beach tourism area but also a natural laboratory. which provides knowledge for visitors in environmental management systems and utilizes the South Sheet Mangrove ecosystem wisely and judiciously. The results of service activities, namely the socialization of the value of mangrove ecotourism, have been delivered to SMP 1 Lembar students, consisting of provider services, regulatory services, supporting services and cultural services. Mangroves can be used as a learning resource, especially in studying Natural Sciences. This is because students will be directly involved with nature so that learning activities become more interesting. In conclusion, this service activity ran smoothly and received a positive response from students and teachers at SMP 1 Lembar.